3D Printed Total Talus Replacement for Avascular Necrosis of the Talus. (December 2020) - Kadakia, Rishin J.; Akoh, Craig C.; Chen, Jie; Sharma, Akhil; Parekh, Selene G.
Background: Talus avascular necrosis (AVN) is a challenging entity to treat. Management options depend on disease severity and functional goals. Total talus replacement (TTR) is a treatment option that maintains joint range of motion. The literature on TTR is limited with variability in implant design and material. The purpose of this study was to evaluate outcomes following TTR with a custom 3D printed metal implant. Methods: Patients who underwent TTR were retrospectively reviewed over a 3-year period. Basic demographic data and comorbidities were collected. Medical records were reviewed to obtain postoperative and preoperative visual analog scale (VAS) scores, Foot and Ankle Outcome Scores (FAOSs), ankle range of motion, and postoperative complications. Statistical analysis was conducted to compare clinical and patient-reported outcomes pre- and postoperatively. Twenty-seven patients underwent TTR for talar AVN with a mean follow-up of 22.2 months. Results: Ankle range of motion remained unchanged postoperatively. VAS pain scores improved postoperatively from 7.1 to 3.9 ( P < .001). FAOSs improved postoperatively with regard to pain ( P < .001), symptoms ( P = .001), quality of life ( P < .001), and activities of daily living ( P < .001). There were 3 complications requiring reoperation in this cohort. Conclusion: 3D printed TTRs represent a unique surgical option for patients with severe talar AVN. Patients in this cohort demonstrated significant improvements in pain scores and patient-reported outcomes. TTR allows for symptomatic improvement with the preservation of motion in individuals with talar collapse and AVN. Level of Evidence: Level IV, retrospective case series.